Factors Associated with Length of Stay of Dengue Hemorrhagic Fever Patients at a Regional General Hospital in Bali - Siada, Nyoman Budiartha; Juanita, Rr Asih (Jurnal Ilmiah Medicamento, 2025)
The World Health Organization (WHO) reported one to five million dengue infections from 2020 to 2022. According to Indonesian Health Profile data in 2020, the province of Bali had the highest Dengue Hemorrhagic Fever (DHF) Incidence Rate (IR), 273.1 morbidity, and a Case Fatality Rate (CFR) of 0.2%. The longer the patient's stay, the greater the costs are incurred for hospital treatment. Therefore, this study aims to analyze the factors influencing the length of stay of DHF patients with complications and comorbidities. This study was an observational study. Medical record data of DHF patients with complications and comorbidities were collected using a retrospective technique from January 2020 to December 2020 during hospitalization at a regional public hospital in Bali. The independent variables in this study include age, the severity of DHF, complications and comorbidities, and the amount of fluid therapy patients use during hospitalization. The dependent variable in this study is the patient's length of stay. The relationship between the independent and dependent variables was analyzed using logistic regression with a significance level set at p<0.05. There were 115 hospitalized DHF patients with complications and comorbidities, consisting of 52% males and 48% females. Most patients were in the age range of 6-11 years (43%). Based on the analysis that has been carried out, there is a factor that is significantly related to the length of stay of DHF patients, namely the use of the amount of fluid therapy (p=0.02). The findings of this study support the evaluation of DHF therapy, particularly in selecting the type and volume of fluids.